Friend or foe: the role of microRNA in chemotherapy resistance - Li, Haoran (Nature Publishing Group, 2013)
Chemotherapy has been widely used in treating cancer patients. Despite the tremendous progress in cancer treatment achieved during the last decades, drug resistance still accounts for most of the tumor relapses in chemotherapy-treated patients. Emerging evidence shows that microRNAs play an important role in regulating the drug sensitivity of tumor cells. However, the mechanism of microRNA-mediated drug resistance is not fully understood. Current data suggest that microRNAs can be categorized as oncogenic or tumor-suppressive based on their functions and targets. In tumor cells undergoing drug treatment, microRNAs can function either by decreasing expression of genes associated with multiple drug resistance or by promoting escape from apoptosis and inducing tumor stem cell development. This review aims to provide an updated understanding of the role of microRNAs in regulating chemotherapy resistance and a discussion of potential therapeutic applications.